PENGARUH KUALITAS PRODUK, PROMOSI DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN BERMOTOR YAMAHA MIO - Yahya Tanjung (Universitas Methodist Indonesia, 2019)
A person's buying behavior towards a product is influenced by many factors. Each individual has different desires and tastes. Product quality is a factor that is very influential on purchasing decisions, besides that there are many other factors that influence the purchasing behavior. This study aims to analyze the influence of product quality, promotion and design on purchasing decisions for Yamaha Mio motorcycle products and analyze the variables that have the most dominant influence on purchasing decisions for Yamaha Mio motorcycle products in the community in the Surakarta region. The population in this study were all consumers of Yamaha Mio motorcycles in the Surakarta region. The sample used was 150 respondents with the Accidental Quota Sampling technique. Data collection techniques with questionnaires, while data analysis techniques using multiple linear regression analysis, classical assumptions (normality test, multicollinearity test, heteroscedasticity test), statistical tests (t test, F test and coefficient of determination). From the results of the classical assumption analysis, the normality test with kolmogorov-smirnov obtained significantly greater than 0.05, which means that the data distribution is normal. Multicollinearity test obtained VIF and Tolerance values ​​close to one so that it can be concluded that the regression model has no multicollinearity problem, while the heteroscedasticity test using the Glejser method states there is no problem. Based on the results of the multiple linear regression analysis of the t test, it was found that partially the quality of the product had a significant effect on purchasing decisions of Yamaha Mio motorcycle products, while promotion and design had a significant effect on the 5% tarap. From the results of the F test that the simultaneous quality of the product, promotion and design significantly influence the purchase decision of Yamaha Mio motorcycle products where the calculated F value> F table. Product quality has the most dominant influence on purchasing decisions for Yamaha Mio motorcycle products. Obtained an R square value of 0.255, which means that the dependent variable can be explained by an independent variable of 25.5% while the remaining 74.5% is explained by other variables outside the model.